RAI PAAR KATILAU: A MODEL OF VALUE TRANSFORMATION DO NOT WANT TO BE LEFT BEHIND IN STRENGTHENING THE SOCIO-ECONOMIC LIFE OF TIBO WOMEN IN KAWANGKOAN MARKET MINAHASA REGENCY - Maria Heny Pratiknjo; Titi Mulyanti; Mahyudin Damis (Lafadz Jaya Publisher, 2023)
Rai Paar Katilau literally means don't want to be left behind, is a cultural value that has a philosophical meaning that living people must do something good. In other words, this cultural value teaches Minahasa people in general to achieve the highest possible success while still alive. For Minahasa women, the call to work outside the home as a tibo workers is a manifestation of a sense of responsibility towards the family. This is also supported by the social system of society which does not question women working outside the home in the public sector with the aim of earning income. In the current era, the level of modernization and information is increasingly globalized, the success of the movement for women's emancipation and awareness of gender roles, the cultural values of Raai Paar Katilau are strengthening in the context of being called Awareness of the right to life from an economic aspect as well as various responsibilities for fulfilling the personal needs of women and tibo worker do their jobs and what and how they work. This research uses qualitative methods, the author's data is obtained through observation techniques and in-depth interviews. In order to match the data with the real situation, the triangulation technique is used.